Fire behaviour of tabique wall – experimental and numerical study - Ferreira, Débora (2016)
This paper presents a study on the behaviour of tabique walls, concerning its fire resistance. Current work is based on the experimental analysis of real scale tabique wall panels. Such wall panels were made in pine wood with an earth-based mortar finishing. In order to assess thickness effect of the earth-based mortar on the fire resistance of the wall, three specimens were tested with different mortar thicknesses of 15, 10 and 5 mm. The experimental specimens were tested in a fire-resistance furnace according to the ISO 834 standard fire curve. Fire resistance of test elements is expressed as the time during which the appropriate criteria have been satisfied so that one can predict the time before collapse, increasing both people and property safety. The obtained results are of great importance as they improve the knowledge on the behaviour of tabique walls subjected to fire conditions. Two performance criteria were verified: the integrity and the insulation criteria. A numerical model was developed in order to assess the tabique wall behaviour under fire conditions, which was validated using experimental results.